1996
DOI: 10.1021/ac9604999
|View full text |Cite
|
Sign up to set email alerts
|

Solid Phase Chemiluminescence Detection Reactors Based on in Situ Polymerized Methacrylate Materials

Abstract: In situ photopolymerized macroporous poly(glycidyl methacrylate-co-trimethylolpropane trimethacrylate) materials, which were prepared in a full factorial experimental synthesis design, were investigated as supports in solid phase chemiluminescence detection reactors. The reactors based on in situ polymerized supports showed higher light generation efficiency than packed bed reactors when evaluated in a flow system based on 1,1′-oxalyldiimidazolyl peroxyoxalate chemiluminescence detection of hydrogen peroxide, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…One of the most popular functional monomers is glycidyl methacrylate (GMA) [9,28,37,39]. Its major advantage is the presence of reactive epoxy groups in its structure that facilitates modification in order to prepare a wide range of functional materials.…”
Section: Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular functional monomers is glycidyl methacrylate (GMA) [9,28,37,39]. Its major advantage is the presence of reactive epoxy groups in its structure that facilitates modification in order to prepare a wide range of functional materials.…”
Section: Monomersmentioning
confidence: 99%
“…Alternatives to EDMA are diethylene and triethylene glycol dimethacrylates (DEGDMA and TEGDMA, respectively) [37,54], trimethylolpropane trimethacrylate (TRIM) [37,39,42], glycerol dimethacrylate (GDMA) [49,59], and 1,4-butanediol dimethacrylate (BDDMA) [49]. Sometimes a mixture of crosslinkers is used for preparation of the methacrylate monoliths.…”
Section: Crosslinkersmentioning
confidence: 99%
“…These applications cover a rather broad range from heterogenized catalysts [66, 71, 82 -87], detection [88], solid-phase extraction [41,89], polymer-supported chemistry [90,91], molecular imprinting [92 -99], to a variety of separations including gas chromatography [100], HPLC, and CEC. Most of these applications have been summarized in a recently published monograph [16].…”
Section: Hplc Applicationsmentioning
confidence: 99%
“…Typically, these experiments are performed using reactors packed with beads that have fluorophores bound to their surface. PontØn et al [83] have reported the use of glycidyl methacrylate-trimethylolpropane trimethacrylate (TRIM, 11) monoliths prepared by photopolymerization within a quartz tube. Both the surface area and degree of functionality of the resulting polymers could easily be adjusted by making changes in the composition of the original polymerization mixture.…”
Section: Solid-phase Detectionmentioning
confidence: 99%